The Impact of Trade Liberalization on the Canadian Labor Market since 1989 - Tian, Meng (Université d'Ottawa | University of Ottawa, 2008)
The Canada-United States Free Trade Agreenlent (FTA) is the most controversial agreement of its kind in Canadian history. This paper examines the impact of tariff liberalization on employment and average annual earnings in the Canadian manufacturing secto